Probiotic Lactobacillus strains isolated from date waste and wastewater for the kidney stone, intestinal oxalate-degradation and antioxidant activity - Ayoub Al Othaim (Journal of King Saud University: Science, 2023)
Lactic acid bacteria (LAB) are probiotic organisms and are promising alternatives to manage kidney stone problems. Oxalate digesting LAB was screened from date wastes and date wastewater. LAB was isolated using De Man, Rogosa and Sharpe agar (MRS agar) medium and was subjected to oxalate degradation assay in a calcium oxalate plate. The strain was further subjected to assay for its capacity to tolerate acidic pH value and bile salt. Then, anti-urolithiatic activity assay was carried out by in vitro analysis. Based on preliminary characteristics, among 62 oxalate degrading strains, twenty-four strains exhibited a greater than 10 mm zone. The potent bacterial strains were identified as Lactobacillus cassei, L. acidophilus, L. gasseri and L. fermentum. Isolates from date wastes showed better antagonistic properties towards bacterial pathogens. At 50 µg Calcium oxalate concentration, 75.6 ± 0.865 degradation was achieved by L acidophilus. LAB isolated from date waste showed promising anti-urolithiasis activity. Hence, date waste may serve as a potential source for LAB probiotics to treat hyperoxaluria.